LEVEL OF ALEXITHYMIA AS A MEDIATOR OF EMPATHY AND COMMUNICATION SATISFACTION - Adiningtyas, Nurul; Astuti, Sri Wahyuning (Universitas Mercu Buana Jakarta, 2024)
The Digital Generation is considered a generation that lacks empathy. Based on the research results, this generation tends to think for themselves. One that makes a person have low empathy is alexithymia, which is a person's lack of ability to identify and describe and identify emotions within themselves. The lack of emotion and the absence of emotion makes satisfaction in communication also low. This study aims to see the level of alexithymia and empathy on communication satisfaction and relationship satisfaction. The research method used is descriptive quantitative. There were 102 research participants using random sampling technique. Data collection used the Alexithymia Scale (α=840) Empathy Scale (α=675) and Communication Satisfaction Scale (α=819). Test results using Path Analysis show that Alexithymia mediates the relationship between empathy and communication satisfaction with a contribution of 83%. It can be concluded that individuals who have high levels of alexithymia have high empathy and communication satisfaction.